SAT0153 Effectiveness of low and high dose methotrexate in combination with adalimumab in a real world setting: results from the corrona rheumatoid arthritis registry. (15th June 2017) - Pappas, D; Griffith, J; Schlacher, CA; Shan, Y; Karki, C; Kremer, JM
Abstract : Background: Combination therapy of methotrexate (MTX) with biologics results in superior outcomes vs. monotherapy. Recent clinical trials have shown that lower MTX doses may be sufficient in patients with rheumatoid arthritis (RA) to achieve similar clinical and patient reported outcomes (PROs) 1, 2 . Objectives: To evaluate whether high MTX dose in combination with adalimumab (ADA) results in improved clinical and PROs compared with low MTX dose. Methods: Adult RA subjects naïve to other monoclonal antibodies, initiating standard dose ADA (40mg q2w) in combination with oral MTX (low dose: ≤12.5 mgs and high dose: ≥15 mgs) during 2003–2016 and had a 6 month follow-up visit were included. The primary outcomes were mean change in clinical disease activity index (CDAI), and PROs (mHAQ, pain, fatigue, morning stiffness) from baseline to 6 months. Secondary outcomes included achievement of remission (CDAI≤2.8)/low disease activity (CDAI≤10). Outcomes were evaluated adjusting for covariates that differed at baseline using mixed model linear regression. Persistency of ADA between the two groups was examined using Kaplan-Meier survival analysis. Results: A total of 519 patients were included: N=101 and N=418 initiated ADA with low and high dose MTX respectively. Patients on high dose MTX were significantly younger (53.3 vs 59.7 years), with lower disease duration of RA (8.8 vs 11.2 years) compared to low dose MTX group. Patients in the high dose group also had higher disease activity (mean CDAI: 20.8 vs 15.4) and more likely to be biologic-naïve (71.3% vs 55.4%), compared to the low dose group (all p<0.05). Unadjusted and adjusted analyses found no sufficient evidence that patients on high dose MTX had a better improvement in the outcomes selected (table). Persistency of ADA did not differ between the two groups. Conclusions: In this real world study, improvements in PROs and achievement of LDA/remission at 6 months were similar in the groups initiating ADA in combination with either low dose or high dose MTX. References: Gurjit S. et al. doi:10.3899/jrheum.151009. Gerd-Rudiger Burmester. et al. doi:10.1136/annrheumdis-2013–204769. Acknowledgements: This study is sponsored by Corrona, LLC. Corrona, LLC has been supported through contracted subscriptions in the last two years by AbbVie, Amgen, BMS, Crescendo, Eli Lilly and Company, Genentech, GSK, Horizon Pharma USA, Janssen, Momenta Pharmaceuticals, Novartis, Pfizer, Roche and UCB. The design, study conduct, and financial support for the study was provided by AbbVie. AbbVie participated in the interpretation of data, review, and approval of the abstract. Disclosure of Interest: D. Pappas Grant/research support from: AbbVie, Inc, Consultant for: AbbVie, Inc, Employee of: Corrona, LLC, J. Griffith Shareholder of: AbbVie, Inc, Employee of: AbbVie, Inc, C. Schlacher Shareholder of: AbbVie, Inc, Employee of: AbbVie, Inc, Y. Shan Employee of: Corrona, LLC, C. Karki Employee of: Corrona, LLC, J. Kremer Shareholder of: Corrona, LLC, Grant/research support from: AbbVie, Genentech, Lilly, Novartis, Pfizer, Consultant for: AbbVie, Amgen, BMS, Genentech, Lilly, Regeneron, Sanofi, Pfizer, Employee of: Corrona, LLC